THE NATURE AND THEORETICAL DESCRIPTION OF THE CONCEPT OF "ECONOMIC COMPETENCE" - M.I.NURMATOVA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The concept of "competence" has been studied by researchers for more than half a century. In the past, competencies in various fields of activity have been explored. In a market economy, it is important to study economic competence among them. The article discusses the essence of economic competence.